The effects of resistance exercise on body composition and physical function in prostate cancer patients undergoing androgen deprivation therapy: an update systematic review and meta-analysis. (31st December 2022) - Tian, Siyu; Ding, Meng; Sun, Hongfu
Abstract: Objective: The aim of the meta-analysis was to explore effects of resistance exercise (RE) on body composition and physical function in patients with prostate cancer (PCa). Data sources: We searched the electronic databases of Pubmed, Embase, Cochrane, and web of science. Published studies have been collected from these databases. Search terms include resistance training, strength training, RE, androgen suppression therapy, androgen deprivation therapy and PCa, with a deadline of 31 March 2022. Main results: These studies showed significant improvements of body composition(Lean body mass MD: 1.12 95% CI [0.48, 1.76], p < 0.01; Body fat rate MD: –1.12 95% CI [–1.99, –0.24], p < 0.05; Appendicular skeletal mass MD: 0.74 95% CI [0.45, 1.03], p < 0.01) and physical function (leg press MD: 77.95 95% CI [38.90, 117.00], p < 0.01; stair climb MD:–0.30 95% CI [–0.49, –0.12], p < 0.01). In addition, the improvement of Body fat mass (MD: –0.21 95% CI [–0.79, 0.37], p > 0.05), 400 m walk (MD: –21.74 95% CI [–45.53, 2.05], p > 0.05) and times up and go (MD: –0.50 95% CI [–1.03, 0.03], p > 0.05) were not obvious. Subgroup analyses showed that RE for ≥ 6 months (compared with RE intervention for < 6 months) and starting exercise immediately after androgen deprivation therapy (ADT) (compared with delayed exercise after ADT) resulted in more significant improvements in body composition. Furthermore, the results showed that the exercise intensity of 8–12 RM significantly improved body composition. Conclusions: RE seems to be a promising approach in order to improve body composition and physical function in PCa patients to offset their treatment-related side effects. RE should be used as a means of rehabilitation and care for PCa. Starting exercise immediately after ADT and extending exercise time while choosing the right intensity can better improve the patients' body composition and function. Registration number: INPLASY202280019